The Postfeminist Masquerade and the Cynical Male Gaze: The Disavowal of Sexual Difference in Lars von Trier’s Breaking the Waves - Tamas NAGYPAL (E-REA)
This article is a commentary on the Lacanian appropriation of Breaking the Waves by Slavoj Zizek, Frances Restuccia and others who argue that the film’s saintly heroine, Bess, performs an authentic feminine act paradoxically in her very suicidal over-identification with her husband’s male chauvinistic desire pressing her to have sex with other men, through which she successfully demonstrates the deadlock of sexual difference and subverts the phallic-masculine symbolic order. By contrast, this paper argues that the heroine is rather trapped in what Angela McRobbie called the postfeminist masquerade, a feminine gender performance that returns to old forms of patriarchal subordination but with an ironic distance, thereby allowing the subject to imagine herself free of the capture of the masculine symbolic universe. In a cynical move which undermines the postfeminist association of irony with freedom, the director equates Bess’s belief in God with her acting for the gaze of his camera, betraying his skepticism about a feminine subject not captured by the cinema’s patriarchal apparatus.